2014
DOI: 10.1111/1756-185x.12527
|View full text |Cite
|
Sign up to set email alerts
|

Bone scintigraphy in axial seronegative spondyloarthritis patients: role in detection of subclinical peripheral arthritis and disease activity

Abstract: The spectrum of joint involvement in seronegative SpAs should not be limited to sacroiliitis. Bone scintigraphy provides a cost-effective method for detecting the extent of involvement in this group of autoimmune systemic diseases (axial SpA) without clinical evidence of peripheral arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 24 publications
(25 reference statements)
0
10
0
5
Order By: Relevance
“…In another study, specificity of quantitative scintigraphy in 30 patients with MRI-positive non-radiographic SpA was calculated as 100%, while sensitivity of the method was only 32% 7. Finally, the diagnostic potential of bone scintigraphy to elucidate unappreciated articular and entheseal involvement in addition to the imaging of the SIJ in SpA was examined and found useful in the study of Gheita et al,8 thus offering an additional benefit of this modality.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, specificity of quantitative scintigraphy in 30 patients with MRI-positive non-radiographic SpA was calculated as 100%, while sensitivity of the method was only 32% 7. Finally, the diagnostic potential of bone scintigraphy to elucidate unappreciated articular and entheseal involvement in addition to the imaging of the SIJ in SpA was examined and found useful in the study of Gheita et al,8 thus offering an additional benefit of this modality.…”
Section: Resultsmentioning
confidence: 99%
“…Level I of the evidence‐based study (Table ) on systemic lupus erythematosus patients without musculoskeletal involvement showed that clinical and physical examinations failed in the detection of subclinical synovitis and tenosynovitis. Most subclinical disease is quantified in the small joints of the feet and hands . Traditionally, physical examinations and laboratory tests are the first choices for detection of synovitis.…”
Section: Discussionmentioning
confidence: 99%
“…Die Daten einer Literaturrecherche aus 2008 legten bereits nahe, dass die Szintigrafie der Sakroiliakalgelenke für die Diagnose einer etablierten AS, einschließlich der Frühdiagnose einer wahrscheinlichen oder vermuteten Sakroiliitis, allenfalls von begrenztem diagnostischen Wert ist [88]. Eine kleinere Studie von 2015 mit nur 20 axSpA-Patienten konnte anhand der Szintigrafie eine subklinische Beteiligung peripherer Gelenke nachweisen [89]. Einen klinischen Stellenwert erhält die Szintigrafie weiterhin zur Abgrenzung unklarer differenzialdiagnostischer Krankheitsbilder.…”
Section: Skelettszintigrafieunclassified